Unifocal Langerhans Cell Histiocytosis of the Superior Oblique Muscle. Issue 3 (May 2015) - Narayan, Daniel; Figueira, Edwin; Kearney, Daniel; McKelvie, Penelope; Davis, Garry; Selva, Dinesh
<x xml:space="preserve">Abstract</x> Orbital Langerhans cell histiocytosis (LCH) without bone involvement is rare. Isolated involvement of an extraocular muscle without bone change, to the best of the authors' knowledge, has not been previously reported. They describe a unique case of unifocal LCH of the superior oblique muscle with no bone involvement. A 16-year-old girl presented with a 2-week history of diplopia and headache. CT and MRI showed an enlarged right superior oblique muscle with no associated bone involvement. Biopsy with partial debulking revealed LCH and staging confirmed unifocal disease. The lesion underwent complete radiologic resolution following surgery. There was no recurrence after 16 months follow up.